Artesunate alleviates the inflammatory response of ulcerative colitis by regulating the expression of miR-155. (1st January 2021) - Yang, Zhao-Bin; Qiu, Lu-Zhen; Chen, Quan; Lin, Jian-Dong
Abstract: Context: Ulcerative colitis (UC) is a recrudescent and chronic inflammatory disease. Artesunate (ART) has shown its anti-inflammatory and antioxidative properties in severe diseases, including UC. Objective: The present study investigates the molecular mechanisms for effects of ART on UC, and the role of miR-155 in this process. Materials and methods: The in vitro UC model was established by using lipopolysaccharide (LPS)-induced RAW264.7 cells. For BALB/c mice model, different concentrations/doses of ART were treated once a day for 7 days. The apoptosis and viability were measured by CCK-8 and flow cytometry assay, respectively. The expressions and concentrations of inflammatory factors were detected by qRT-PCR and ELISA, respectively. Colon tissues of mice were used for detecting the activity of MPO, and the histological changes were observed by H&E staining. Results: The IC50 of ART for RAW264.7 cells was 107.3 μg/mL. In LPS-induced cells, ART treatment inhibited the cell apoptosis and promoted cell viability compared with the model group. Besides, ART treatment also reduced the expressions of pro-inflammatory factors and miR-155. However, overexpression of miR-155 showed opposite effects and attenuated the effects of ART. Meanwhile, inhibiting miR-155 expression also improved the inflammatory response induced by LPS. In UC mice model, ART treatment also alleviated the mice's survival and alleviated the inflammatory response. In addition, the expression of p-NF-κB was suppressed by ART. Conclusion: ART reduced the inflammatory response by inhibiting the expression of miR-155 in UC to inhibit the NF-κB pathway. This research showed ART might have potential in UC treatment.